2018
DOI: 10.18488/journal.8.2018.62.110.120
|View full text |Cite
|
Sign up to set email alerts
|

Nigerian Enterprise Sector and Policy Uncertainty

Abstract: This study evaluates the Nigerian enterprise sector and policy uncertainty using the World Bank enterprise survey data for Nigeria 2010. Using the multinomial logistic regression model and the multivariate analysis to specifically analyze the impact of policy uncertainty on the enterprise sector and the factors that have influenced the growth of the Nigerian enterprise sector, the findings show that tax rate, customs and trade regulations and macroeconomic environment have impacted on the medium and large ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The policy implication suggested that Nigeria should diversify its export strategy to protect against contemporaneous effect of global EPU. In EPU-Enterprises context , Ukwueze et al. (2018)'s study confirmed that policy uncertainty has a significant negative effect on the medium and large enterprises sector in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 86%
“…The policy implication suggested that Nigeria should diversify its export strategy to protect against contemporaneous effect of global EPU. In EPU-Enterprises context , Ukwueze et al. (2018)'s study confirmed that policy uncertainty has a significant negative effect on the medium and large enterprises sector in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Majority of these studies focused predominantly on the advanced economies of United States, Canada, United Kingdom, Europe, China, Japan, Australia and Korea. In Nigeria, Ukwueze et al (2018) examined the impact of policy uncertainty on enterprise sector using a multinomial logistic regression model and data from the World Bank 2010 enterprise survey. The study found that policy uncertainty impacts negatively on medium and large sector enterprises.…”
Section: An Overview Of the Literaturementioning
confidence: 99%
“…Arouri et al (2016) also used OLS regression to fi nd that an increase in policy uncertainty decreases stock returns signifi cantly in the U.S., while Gulen and Ion (2016) also found that EPU depressed U.S. corporate investment. Ukwueze et al (2018) used a multinomial logistic regression model to show that uncertainty impacts negatively on medium and large enterprises in Nigeria, while CBN (2015) used GARCH framework to show that in the period 2000Q1-2015Q1, monetary policy eff ectiveness in Nigeria was not signifi cantly undermined by macroeconomic uncertainty.…”
Section: Empirical Literaturementioning
confidence: 99%